The Best of Both Worlds: Unlocking the Potential of Hybrid Work for Software Engineers - Houck, Brian; Yelin, Henry; Butler, Jenna; Forsgren, Nicole; McMartin, Alison (2023)
Everything we thought we knew about how developers work is in a state of change. The Era of Hybrid Work has begun, and it brings new challenges and opportunities along with it. In this paper, we will explore the top challenges that developers are facing in their jobs, the biggest barriers to their productivity and what individuals, teams and organizations can do about it. The SPACE framework posits that developer productivity spans many dimensions, and these next pages show that the challenges developers face are similarly multi-faceted. Since the pandemic, software engineering has changed in many ways, but one of the most notable changes is the ability for people to choose where they work. Companies now understand the importance of offering flexibility in work location to attract and retain top talent. In fact, our research found that developers who are dissatisfied with their ability to choose when and where to work are more than two times as likely to be actively seeking new employment opportunities. However, allowing flexibility in work location comes with tradeoffs and unique challenges, and companies must be equipped to address these to maintain a successful and efficient workforce. In general, there is an opportunity to further accentuate the positive elements of hybrid work, while also addressing some of hybrid work’s unique challenges. Current research shows we have not yet cracked the code on hybrid work. It still holds the promise of the best of both worlds – a vibrant, connected work life with social work relationships and productive impact, and an interwoven life and work balance that allows for loads of laundry between meetings and attending your kid’s soccer game – but we haven’t realized that promise yet. Instead, many people feel the tension: going to the office when no one is there, unable to separate work from life, feeling “always on” and experiencing “productivity paranoia” (a commonly reported tension between what managers think is happening and what employees are actually doing). More research is needed to understand how hybrid work can empower everyone to both live the life they want and be productive at work. This study aims to identify the unique challenges of hybrid work in software engineering by analyzing the results of over 3,400 survey responses conducted across 28 companies in seven countries, asking developers not just where they work, but is it really working for them?